Older generation in region’s labor market: the analysis of demographic and economic components - N. V. Borovskikh; E. A. Kipervar (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses the demographic and economic aspects of the labor market of the Omsk region associated with the use of labor of older people. The paper analyzes the demographic and economic situation on the labor market that has developed on the regional labor market, assesses the natural movement of the population, reveals a tendency of demographic aging of the population, which is manifested in the growth of the population of older ages against the background of a relatively low birth rate. The paper concluded that the high economic activity of people in the older age groups is mainly due to the causes of socio-economic nature. The socio-economic factors that determine the growth of employment in the older population group are determined, the dominant ones are: lack of funds for current consumption, desire to be involved in the society, desire to create savings for the future. The importance of the older generation in the social development of the region is noted and the role of participation of this group in labor activity is determined, which necessitates the creation of favorable conditions for the realization of its resource potential, which should involve the development and implementation of appropriate health-saving programs, as well as a change in the socio-cultural paradigm of «old age» that creates representation of the elderly as an unproductive part of society